Ways to Enhance the Performance of an Organization: Teachings from PT Pupuk Indonesia Logistik (PILOG) - Asrul; Agung Iman Santoso; Nur Imam Saifuloh; Andi Muhammad Sadli (Journal of Managerial Sciences and Studies, 2024)
The organizational performance of PT Pupuk Indonesia Logistik (PILOG) is declining due to a number of problems, including inadequate human resource development and acquisition. Achieving corporate objectives and enhancing organizational performance depend on having high-quality people resources. This study will examine the impact of pawnshops, competency, and organizational support on enhancing organizational performance within the corporation using multiple linear regression analysis. The study's findings, which totaled 0.187, 0.477, and 0.298, showed that organizational performance was positively impacted by procurement, competence, and organizational support, all partially and simultaneously.